Heterotelechelic Polymers by Ring‐Opening Metathesis and Regioselective Chain Transfer. Issue 4 (27th December 2017) - Liu, Peng; Yasir, Mohammad; Ruggi, Albert; Kilbinger, Andreas F. M.
Abstract: Heterotelechelic polymers were synthesized by a kinetic telechelic ring‐opening metathesis polymerization method relying on the regioselective cross‐metathesis of the propagating Grubbs' first‐generation catalyst with cinnamyl alcohol derivatives. This procedure allowed the synthesis of hetero‐bis‐end‐functional polymers in a one‐pot setup. The molecular weight of the polymers could be controlled by varying the ratio between cinnamyl alcohol derivatives and monomer. The end functional groups can be changed using different aromatically substituted cinnamyl alcohol derivatives. Different monomers were investigated and the presence of the functional groups was shown by NMR spectroscopy and MALDI‐ToF mass spectrometry. Labeling experiments with dyes were conducted to demonstrate the orthogonal addressability of both chain ends of the heterotelechelic polymers obtained. Abstract : Heterotelechelic polymers were synthesized by a kinetic telechelic ring‐opening metathesis polymerization method relying on the regioselective cross‐metathesis of the propagating Grubbs' first‐generation (G1) catalyst with cinnamyl alcohol derivatives. The molecular weight of the polymers could be controlled by varying the ratio between cinnamyl alcohol derivatives and monomer.